Logística de distribuição: um framework para a implementação de soluções satisfatórias na perspectiva do serviço ao cliente em cooperativas agroindustriais - Oliveira, Luiz Felipe de (Universidade do Vale do Rio dos Sinos, 2025)
The general objective of this work is to propose a framework to contribute to the effectiveness of customer service provided by agro-industrial cooperatives through satisfactory solutions in their distribution logistics. Distribution logistics and customer satisfaction are topics widely discussed in the literature; however, their specific application to the context of cooperatives remains little explored, giving relevance to the research, since there is no structure that relates customer requirements, competitive dimensions with theories and production systems. To carry out the study, the Design Science Research (DSR) methodology was used, which allows the construction of artifacts that interact with the real environment. Data collection involved different actors in the logistics chain who are managers of agro-industrial cooperatives, in order to understand the main difficulties and needs related to customer service in distribution logistics. In addition, as a validation step, the framework was submitted to validation by a focus group, composed of professors and experts, who provided contributions to the refinement of the model. The final artifact projects an approach based on the synergy between methods derived from theories and systems, including the Theory of Constraints (TOC), the Toyota Production System (TPS), Total Productive Maintenance (TPM) and World Class Manufacturing (WCM) with the aim of achieving customer satisfaction through the requirements desired by customers in distribution logistics. Among the main results found, the importance of structuring a model that integrates performance indicators and the SLA (Service Level Agreement) as a type of ‘agreement’ serving to externalize what the customer wants stands out. Finally, the development of the artifact offers a structure so that cooperative managers can achieve customer satisfaction and what needs to be considered to reach this specific objective through the use of satisfactory solutions.
Keywords: Logística de distribuição; Service Level Agreement (SLA); Serviço ao cliente; Satisfação de clientes; Cooperativas agroindustriais; Design Science Research (DSR); Outbound logistics; Service Level Agreement (SLA); Customer service; Customer satisfaction; Agro-industrial cooperatives; ACCNPQ::Ciências Sociais Aplicadas::Administração